Pendekatan Psikologi Islam Terhadap Pencurian, Perampokan dan Korupsi: Tinjauan Preventif, Kuratif dan Rekonstruktif - Fathya Putri Kamilla; Rahma Fithri; Vivik Shofiah; Khairunnas Rajab (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study explores the perspective of Islamic psychology in responding to criminal behaviors such as theft, robbery, and corruption through three main strategies: prevention, curative intervention, and reconstruction. Using a library research design with a descriptive-analytical approach, the paper examines scholarly works related to Islamic psychology, Islamic law, moral education, and criminal conduct. The analysis indicates that preventive efforts are most effective when they are rooted in strengthening faith, moral and character development, family-based socialization, and the establishment of fair socio-economic structures. Curative interventions focus on spiritual and psychological recovery through practices such as muhasabah (self-introspection), taubat nasuha (sincere repentance), and Islamic counseling, alongside social reintegration initiatives including skills training and economic empowerment. Reconstruction emphasizes a restorative justice approach that actively involves victims, offenders, and the wider community in processes of reconciliation, healing, and the restoration of social trust. Overall, Islamic psychology offers a comprehensive framework that integrates spiritual, moral, and psychological dimensions to prevent, address, and rehabilitate criminal behavior, while providing both theoretical insights and practical strategies for cultivating just, ethical, and socially cohesive societies.